Speech Intelligibility in Severe Adductor Spasmodic Dysphonia. - Bender, Brenda K.; Cannito, Michael P.; Murry, Thomas (Journal of Speech, Language & Hearing Research, 2004)
This study compared speech intelligibility in nondisabled speakers and speakers with adductor spasmodic dysphonia (ADSD) before and after botulinum toxin (Botox) injection. Standard speech samples were obtained from 10 speakers diagnosed with severe ADSD prior to and 1 month following Botox injection, as well as from 10 age- and gender-matched healthy adults. This yielded 3 speaking conditions: pre-Botox injection, post-Botox injection, and normal control. Thirty phrases were extracted from the speech samples and arranged in a counterbalanced listening experiment. Thirty students, reporting little experience with distorted speech, served as listeners. Each listener's response was scored for words correctly identified using a liberal scoring criterion yielding a percentage of words correctly identified for each speaker. The results indicated that the speakers with ADSD were significantly more intelligible in the post-Botox condition than in the pre-Botox condition. The results also indicated that healthy speakers were significantly more intelligible than the speakers in both the preand post-Botox conditions. In general, these results indicated that intelligibility is affected in severe ADSD and that the use of Botox injection in ADSD improves intelligibility scores. However, the results also indicated that the use of Botox injection does not result in speech intelligibility similar to that of normal, non- ADSD speakers. Reprinted by permission of the publisher.